A study on abortion in Singapore : perception of internalized abortion stigma - Lim, Joanna Thai Yin (2015)
Stigma plays an important aspect in affecting one’s life chances, whether referring to careers, social ties, psychological wellbeing or life itself. Abortion taints the social identity of womanhood and stigmatizes the women in daily social context. By understanding the perspectives of women who had abortion through the counsellors, who are intimately privy to their lives, could help to illuminate on the predicament of these women and identify potential assistance that is lacking locally. The research first explored on the themes of stigma as a social process and tries to identity the types of stigma that exists in Singapore. Findings have shown that the perception of internalized abortion stigma exists, however its pervasiveness is not as pronounced as it would be in a legally restricted setting. Another stigma identified is stigma associated with unintended pregnancy. It informs abortion decision and lowers the social status of women who had abortion.